2013
DOI: 10.4103/0250-474x.113531
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Clinical Pharmacy Management System in Improving the Rational Drug Use in Department of General Surgery

Abstract: Hospital information system is widely used to improve work efficiency of hospitals in China. However, it is lack of the function providing pharmaceutical information service for clinical pharmacists. A novel clinical pharmacy management system developed by our hospital was introduced to improve the work efficiency of clinical pharmacists in our hospital and to carry out large sample statistical analyzes by providing pharmacy information services and promoting rational drug use. Clinical pharmacy management sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Besides, only 65 out of 300 hospitals were admitted in this study, which was mainly due to three reasons: (1) the lack of a fully-functional pharmacy management system in certain hospitals that were excluded from this study; (2) the concern for release of sensitive medical data; and (3) the stratified sampling method, which required a ratio of the number of tertiary hospitals to the number of secondary hospitals equaling about 9/10. A computerized pharmacy management system plays important roles in pharmacy validation and concurrent prescription monitoring with improved patient outcomes [ 17 ]. However, more than 50 hospitals that could not participate in this study lacked a functional pharmacy module in their hospital information systems during the study periods, especially in 2010.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, only 65 out of 300 hospitals were admitted in this study, which was mainly due to three reasons: (1) the lack of a fully-functional pharmacy management system in certain hospitals that were excluded from this study; (2) the concern for release of sensitive medical data; and (3) the stratified sampling method, which required a ratio of the number of tertiary hospitals to the number of secondary hospitals equaling about 9/10. A computerized pharmacy management system plays important roles in pharmacy validation and concurrent prescription monitoring with improved patient outcomes [ 17 ]. However, more than 50 hospitals that could not participate in this study lacked a functional pharmacy module in their hospital information systems during the study periods, especially in 2010.…”
Section: Discussionmentioning
confidence: 99%
“…The rapid increase in e-health service has resulted in the implementation of the rational antibiotic use system (RAUS) into China’s hospitals. There are many forms of RAUSs with different functions, such as the Prescription Antibiotic Monitoring Program, the Pharmacy Management System, the Prescription Automatic Screening System and the Computerized Clinical Decision Support [16,17,18,19,20,21,22]. The functions can be summarized into: prescribing behavior monitoring, antibiotic information consultation and medication prescription support.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, in the United States, the Prescription Antibiotic Monitoring Program is widely used to address the diversion of prescription antibiotics and the abuse of antibiotic, which assists doctors in identifying antibiotic-seeking behaviors and avoid adverse antibiotic interactions effectively [18]. From a clinical perspective, a study of the Pharmacy Management System in the department of general surgery in a Chinese hospital reported that this system can standardize antibiotic accuracy apparently by improving the prescribing behaviors of doctors [16]. Another study of a Chinese hospital also verified that the introduction of the Prescription Automatic Screening System could improve pharmacy administration and result in a decrease in negative pharmacy events and enhance the rate in rational prescriptions of doctors [19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Internationally, there are corresponding studies on pharmacists’ influences on prescribing [ 24 ], rational drug use [ 25 ] and opinions on adverse drug reaction reporting [ 26 ]. However, there are few studies on hospital pharmacists’ understanding about the NEMS.…”
Section: Introductionmentioning
confidence: 99%